Investigation of Spintronic Properties of Transition Metal Doped ZnO Thin Films Produced by Sol-Gel Spin Coating - Nuray Altınölçek; Cengiz Akay; Zafer Gültekin (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2024)
Transition metal-doped diluted semiconductor materials have attracted significant interest in spintronic applications. In order to investigate the structural, optical, electrochemical, and magnetic properties of these diluted magnetic semiconductors, transition metal-doped ZnO thin films were successfully produced at room temperature using a low-cost sol-gel spin coating technique with the same molar ratios. XRD analyses revealed that all samples adopted the crystal structure of ZnO. Optical measurements indicated high transparency in the visible region for all samples, while electrical measurements confirmed that all samples were n-type semiconductors. Finally, magnetic measurements showed that pure ZnO and Al-doped ZnO exhibited diamagnetic behavior, while Ni and Co doped ZnO displayed magnetic behavior. These results show that Co and Ni-doped ZnO films can be used as diluted magnetic semiconductor materials in spintronic applications.